Naguvanahaili screening - Vishwanath NS; Nagaraj MN; Swamy Sridhar CV; Satyan HS (Journal of All India Institute of Speech and Hearing, 1971)
This is a report on the collaborative project with the Junior Jaycees of Mysoreto screen the school going children for speech and hearing problems in a nearbyvillage. This village, was selected because of the following reasons.